Design and Development of Computer Specification Recommendation System Based on User Budget With Genetic Algorithm - Michael Michael; Winarno Winarno (Universitas Multimedia Nusantara, 2018)
There are a lot of things that must be considered when determining specifications of computer components to make sure those components chose are working compatible. According to a survey conducted to 78 respondents, about 72.5% of the respondents prefer to buy a built-up computer. The reason is because of a lack of knowledge of computer components and how to assemble computer properly. This research aimed to develop a recommendation system that able to give recommendation of buying computer based on compatible components to be assembled, with the available budget, so that people who do not know computer components can also buy a assembled computer. The Genetic Algorithm was chosen for making this recommendation system because this Algorithm gives more alternative solutions through the process of crossover and mutation compared to the Greedy Algorithm which doesn’t produce a solution by trying all alternative solution nor Exhaustive Search on Brute Force Algorithm which takes a long time to find optimum solution. The recommendation system of computer components specifications based on the budget available has been successfully developed using Genetic Algorithm and achieved 75.75% user satisfaction. Index Terms— Computer Components, Genetic Algorithm, Greedy Algorithm, Recommendation System.